The Battle of France, 1940 - Goutard, Adolphe; Translated by Burgess, A. R. P.; Foreword by Liddell Hart, B. H. (Rawalpindi Army Education Press, 1958)
Reassessment of the fall of France in 1940. Over-all campaign plans of Germany are compared with those of France and her allies, and each battle is analyzed for its part in the fall.
Include Maps, Bibliography and Index.
Keywords: World War (1939-1945) -- Military campaigns -- Western Front (World War (1939-1945))